Characterization of surface properties of Inner Mongolia coal using FTIR and XPS. Issue 11 (3rd June 2017) - Xia, W.; Zhang, W.
ABSTRACT: Fourier transform infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy (XPS) were used to indicate the surface properties of Inner Mongolia high-ash coal in China. The results of FTIR and XPS showed that there were few hydrophilic functional groups but many hydrophobic functional groups on high-ash coal surface. Meanwhile, the primary minerals in coal were kaolin, such as SiO2 and Al2 O3 . Throughout this paper, it was found that the natural hydrophobicity of Inner Mongolia coal was high but the kaolin may have negative effects in the clean coal quality.